(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article deals with the special place in the range of simile is occupied by comparisons based on the use of proper names; comparisons of this type fulfill important textual functions, both at the level of its content and structure, and can be constructed not only according to classical traditional models, but also according to special non-traditional models.